Bundle throne : preloved apparel / Muhammad Ridzuan Mohd Zainuddin ... [et al.] - Mohd Zainuddin, Muhammad Ridwan; Muhaimi, Muhammad Danish; Zaihan, Muhammad Muizuddin; Amri, Afif; Rafik Ahmad, Ahmad Nabil Arif; Rosman, Muhammad Aiamn Alif (2021)
The name Bundle Throne was selected from the words "throne" which mean a ceremonial chair for a high figure such as king. Our ambition is to be one of the top thrift shops in Malaysia. It is very challenging in this industry because we need to compete with others thrift shop and apparel shop such as Round Dua, Kocey Garage, Padini and others. In order to thrive in this business, we need to be active and promote our business on variety of platforms. we also need to keep our item up to date in order to attract more customers. Then, we always make sure that our product is in good condition and clean. We always wash the product first before sold it to the customers. Others than that, we also need to keep update our knowledge on product and our market price based on present time. Whenever we see other opportunities to make this business success and wider, we will take it without any doubt. We also sometime collaborate with others thrift shop while doing live on media social to increase our sell and customers. We always remember a say, "If you want to go fast, go alone. But if you want to go far, go together". We successfully start this business also because of our surrounding support from our family and friends. We intend to keep operate this business until the end